2021
DOI: 10.1155/2021/5529486
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of circRNA as a Novel Diagnostic Biomarker in Cervical Cancer

Abstract: Cervical cancer is the fourth most common cancer among females worldwide. In spite of advances in detection and treatment, it is still one of the most dangerous gynecological malignancies in the world, especially in developing countries, and seriously threatens human health. Circular RNA (circRNA) is a special new type of endogenous noncoding RNA discovered recently. They form a covalently closed continuous loop and are specifically expressed in the eukaryotic transcriptome. With further understanding of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Dysregulated expression of circRNAs has been systematically explored in cervical cancer 100 , 101 , which is one of the most malignant forms of cancer in females 102 . Multiple studies have also highlighted the roles of these circRNAs as potential diagnostic markers in cervical cancer 103 , 104 . circRNA hsa_circ_0023404 has been reported to mediate tumor formation.…”
Section: Functional Mechanisms Of Circrnas Associated With Hippo-yap ...mentioning
confidence: 99%
“…Dysregulated expression of circRNAs has been systematically explored in cervical cancer 100 , 101 , which is one of the most malignant forms of cancer in females 102 . Multiple studies have also highlighted the roles of these circRNAs as potential diagnostic markers in cervical cancer 103 , 104 . circRNA hsa_circ_0023404 has been reported to mediate tumor formation.…”
Section: Functional Mechanisms Of Circrnas Associated With Hippo-yap ...mentioning
confidence: 99%
“… 217 , 223 They lack protein encoding capacity and they have a closed loop structure. 224 Recent studies have revealed the role of circRNAs in HCC. A variety of molecular pathways including miRNAs, Raf1, PDK1 and RAB1A are modulated by circRNAs in HCC.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“…In recent years, with the rapid development of bioinformatic analysis and RNA sequencing technologies, the crucial regulatory role of circRNAs has been explored in a series of tumors. [22][23][24] Chen et al found that circCAMSAP1 expression markedly increased within human OSA cells and tissue, which was closely related to OSA progression. 25 More recently, Qiu et al 26 established a circRNA-miRNA-mRNA network in OSA, in which four mRNAs were suggested as the overall survival-related mRNAs according to survival analysis.…”
Section: Discussionmentioning
confidence: 99%